The genus Orthoseira (Orthoseiraceae, Bacillariophyta) in Papua New Guinea with the description of two new species - Natalia Kochman-Kędziora; Bart Van de Vijver (Plant Ecology and Evolution, 2024)
Background and aims – The genus Orthoseira is generally known to be typically aerophilous. Despite the worldwide occurrence of the genus, most of the Orthoseira species seem to have a rather restricted biogeographic distribution, often being part of an endemic diatom flora. During a survey of the aerophilic diatom flora in Papua New Guinea (Karkar Island, Boisa Island), four morphologically distinct Orthoseira taxa have been observed. Material and methods – The morphology of four Orthoseira species was investigated in detail using light microscopy (LM) and scanning electron microscopy (SEM). Key results – The morphology of all four species is discussed and compared to known species worldwide. The main differences between the species include: the presence and shape of linking structures, the number of rows of perforations on the copulae, presence/absence of internal caverns and the external structure of the carinoportulae. Two species, with a unique set of features, are described as new to science: Orthoseira iserentantii sp. nov. and Orthoseira papuensis sp. nov. Conclusions – The observation of four Orthoseira species, including two species new to science, confirms that the diversity of the genus Orthoseira is underestimated.